DOI: 10.22215/etd/2016-11522
|View full text |Cite
|
Sign up to set email alerts
|

Telltale Gait: The Role of Nonverbal Cues in Perceptions of Personality and Vulnerability

Abstract: Non-verbal behaviour often provides one of the first opportunities to make socially relevant judgments. For example, gait has been shown to inadvertently signal information about personality and vulnerability. Although non-verbal cues such as gait appear to signal socially relevant information, researchers have identified distinct differences in the ability of observers to accurately perceive these cues. Based on this research, Study 1 examined the personalities and victimization histories of walkers in relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(19 citation statements)
references
References 171 publications
(395 reference statements)
1
17
1
Order By: Relevance
“…Their results demonstrated that when the traits of the Dark Triad were controlled for, sadistic traits significantly predicted both a preference for killing bugs and hurting others, further corroborating the appropriateness of the Dark Tetrad . Given that the Dark Tetrad traits seemingly all relate strongly to aggressive and/or malignant behaviours, it is not surprising that the traits positively correlate with one another (Porter et al, 2014;Ritchie, 2016;Ritchie et al, 2019). Porter et al (2014) for example, found that psychopathy was most strongly related to Machiavellianism (r = .69, p < .001), followed by psychopathy and narcissism (r = .39, p < .001) and finally, Machiavellianism and narcissism (r = .…”
Section: Dark Personality Traitsmentioning
confidence: 99%
See 4 more Smart Citations
“…Their results demonstrated that when the traits of the Dark Triad were controlled for, sadistic traits significantly predicted both a preference for killing bugs and hurting others, further corroborating the appropriateness of the Dark Tetrad . Given that the Dark Tetrad traits seemingly all relate strongly to aggressive and/or malignant behaviours, it is not surprising that the traits positively correlate with one another (Porter et al, 2014;Ritchie, 2016;Ritchie et al, 2019). Porter et al (2014) for example, found that psychopathy was most strongly related to Machiavellianism (r = .69, p < .001), followed by psychopathy and narcissism (r = .39, p < .001) and finally, Machiavellianism and narcissism (r = .…”
Section: Dark Personality Traitsmentioning
confidence: 99%
“…Research within this area has been somewhat mixed however; while some studies have not been able to replicate the association between submissiveness and past victimization (e.g., Blaskovits & Bennell, 2019), other researchers have been able to demonstrate these relations (e.g., Beauregard et al, 2007;Ritchie, 2016;Stevens, 1994).…”
Section: Individual Characteristics and Behavioural Vulnerability Cuesmentioning
confidence: 99%
See 3 more Smart Citations